Flexural properties of electrospun polymethyl methacrylate microfiber-reinforced BisGMA for dental post prefabrication - Djustiana, Nina; Faza, Yanwar; Cahyanto, Arief (Padjadjaran Journal of Dentistry, 2021)
Introduction: A dental post is a restoration to preserve the remaining tooth structure thus can be functioned normally. Many researchers suggested a fiber dental post due to its biomechanical properties that are similar to dentin structure. This study aims to analyse the flexural properties of electrospun polymethyl methacrylate microfiber-reinforced BisGMA for dental post prefabrication. Methods: The sample used was following the ADA guideline, as well as for the number of samples. The sample size was 25×2×2mm, which is close to the average dental post size. PMMA microfibers were prepared by dissolving heat cure PMMA powder with 99% acetone, then electrospinning with a rotary collector. Acquired PMMA microfibers were immersed into the resin matrix containing BisGMA, camphorquinone, and 2-dimethylaminoethyl methacrylate (DMAEMA) as a monomer, initiator, and co-initiator, respectively, to prepare the dental posts. Results: PMMA microfibers structure and surface fracture of dental posts were confirmed by Scanning Electron Microscopy (SEM). PMMA microfibers show unaligned fiber morphology with an approximate diameter size of 1-5 µm.  A universal testing machine was used to measure the dental post's flexural properties (flexural strength and flexural modulus). Dental posts with PMMA fibers showed higher flexural strength (83.5 ± 10.7 MPa) compared to the dental post without PMMA fibers (61.7 ± 3.03 MPa) with a p-value <0.05. On the other hand, PMMA fibers' addition did not significantly increase the dental post's flexural modulus. Conclusion: The PMMA microfibers can intimately adhere to the BisGMA mixture as the resin matrix. Therefore, the PMMA microfiber significantly improves the flexural strength of the BisGMA for dental post prefabrication.